حصر وتعريف أنواع الأعشاب في بساتين الحمضيات في منطقة اللاذقية - طباش, سمير; حداد, دينا; فنده, وسيم (Latakia University Journal -Biological Sciences Series, 2017)
شملت هذه الدراسة حصر وتعريف 80 نوعاً وتحت نوع واحد من الأعشاب تنتمي لـ 64 جنساً موزعة على 28 فصيلة ضمن ثلاثة بساتين للحمضيات في منطقة اللاذقية على مدار أربعة فصول خلال الفترة الواقعة من أيلول 2014 حتى آب2015. تم حساب كل من الكثافة والكثافة النسبية والتردد والتردد النسبي لكل نوع عشبي لمعرفة تركيب الغطاء العشبي وأهمية الأنواع المنتشرة. كانت نسبة الأنواع التابعة لأحاديات الفلقة 24.69%، أما التابعة لثنائيات الفلقة كانت نسبتها 75.31%، وشكلت الأنواع الحولية نسبة كبيرة بلغت 85.19% والمعمرة 13.58% وثنائية الحول 1.23%. دلت النتائج أن أكثر أنواع الأعشاب الموجودة في بساتين الحمضيات تتبع الفصيلة الكلئية (Poaceae)، حيث تضمنت 17 نوعاً وتحت نوع واحد، وتلتها الفصيلة الفولية (Fabaceae) 9 أنواع والفصيلة النجمية (Asteraceae) 8 أنواع والفصيلة الحليبية (Euphorbiaceae) 7 أنواع. وكان أكثر أنواع أحادية الفلقة كثافةً نوع السعد Cyperus rotundus L. بكثافة بلغت 20.2 نبات/م2 خلال فصل الصيف، أما أكثر أعشاب ثنائيات الفلقة كثافةً عشبة حشيشة الزئبق Mercurialis annua L. بكثافة59.27 نبات/م2خلال فصل الخريف. ومن أهم نتائج الدراسة أيضا إضافة 3 أنواع، وتحت نوع واحد من الفصيلة الكلئية (Poaceae) للفلورا السورية. This study included the survey and identification of 80 species and one sub species of weeds which belong to 64 gender, and 28 families in three citrus orchard in Lattakias region during four seasons in the period from September 2014 to August 2015. The density, relative density, frequency and relative frequency were counted for each one of the weed species to know the structure of weed cover and the importance of the common species. The average of species relating to monocotyledon was 24.69%, but dicotyledon was 75.31%. Annual species formed a high average 85.13% while perennial formed 13.58% and biennial 1,23%. The results showed that most of weed species which exist in the citrus orchards belong to Poaceae family, which includes 17 species and one sub species followed by 9 species of Fabaceae, 8 species of Asteraceae and 7 species of Euphorbiaceae. Cyperus rotundus L. was the most common Monocotyledon species with density average 20.2 plant.m-2 during summer. But Mercurials annua L. was the most common dicotyledon species with density average 59.25 plant.m-2 during Autum. The most important result of this study was the addition of 3 species and one sub species from Poaceae family to the flora of Syria.